HERBERT SPENCER’S INFLUENCE IN EL TIEMPO (1899-1900). A review of the nation, society and the costa rican culture - Urbina Gaitán, Chester (2012)
Some of the intellectuals who wrote in the newspaper El Tiempo (1899-1900), did so under the influence of Herbert Spencer’s, thought to criticize the myth of the peaceful nature of Costa Ricans, exalting individualism, liberalism such as “laissez faire” and social moralizing. Also, repudiated liberal democracy and expressed confidence in a tiny Costa Rican national identity.